1986
DOI: 10.1007/bf00911174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a preventive social problem solving intervention on children's coping with middle‐school stressors

Abstract: Children receiving 1 year or 1/2 year of a preventive social problem solving program in elementary school were compared with each other and with a no-treatment group upon entry into middle school. One year of training was significantly related to reductions in the severity of a variety of middle-school stressors. Most importantly, a clear mediating role for social problem solving (SPS) skills was found. Children lacking in SPS skills were more likely to experience intense stressors; however, possessing the ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 22 publications
2
65
1
1
Order By: Relevance
“…Fourth, contrary to other studies that found cognitive resources to be a relevant resource for coping with stress (Carson & Johnson, 1985;Elias, Gara, Ubriaco, & Rothman, 1986;Giammatteo & Giammatteo, 1980;Schlossberg, 1981), both cognitive resources measured in this study did not significantly moderate increase in stress. Future studies should better define this wide category of stress-coping resources (cognitive resources) and measure different mental resources (problem-solving ability, managing resources such as time and energy and cognitive means) while crossing them with different stressors (e.g., resources with cognitive tasks vs. physical tasks).…”
Section: Limitationscontrasting
confidence: 83%
See 1 more Smart Citation
“…Fourth, contrary to other studies that found cognitive resources to be a relevant resource for coping with stress (Carson & Johnson, 1985;Elias, Gara, Ubriaco, & Rothman, 1986;Giammatteo & Giammatteo, 1980;Schlossberg, 1981), both cognitive resources measured in this study did not significantly moderate increase in stress. Future studies should better define this wide category of stress-coping resources (cognitive resources) and measure different mental resources (problem-solving ability, managing resources such as time and energy and cognitive means) while crossing them with different stressors (e.g., resources with cognitive tasks vs. physical tasks).…”
Section: Limitationscontrasting
confidence: 83%
“…For example, Beurneister, Bratslavsky, Muraven, and Tice (1998) illustrated that cognitive resources are related to resource energy, which can be utilized to explain some cognitive processes. For example, problemsolving ability is a resource that helps in coping with stress (Carson & Johnson, 1985;Elias, Gara, Ubriaco, & Rothman, 1986), as is the ability to manage resources such as time and energy (Giammatteo & Giammatteo 1980;Schlossberg, 1981). Tversky and Kahneman (1974) posited that people use cognitive means in order to obviate the need for further costly processing.…”
Section: Cognitive Resourcesmentioning
confidence: 98%
“…30 Originally developed for work with youths to prevent drug and alcohol use, training in the use of coping skills can teach personal and social behaviors that can assist individuals in dealing with potential stressors they encounter in their daily lives and the stress reactions that may result from these situations. 31 In children and youths without diabetes, such interventions have been demonstrated to reduce substance abuse, 32 improve social adjustment, 33 prevent smoking, 34 and reduce responses to stressors. 34 The skills that are taught include social problem solving, communication skills training (e.g., assertiveness and social skills training), stress management, and cognitive-behavioral modification.…”
Section: Coping Skills Trainingmentioning
confidence: 99%
“…31 In children and youths without diabetes, such interventions have been demonstrated to reduce substance abuse, 32 improve social adjustment, 33 prevent smoking, 34 and reduce responses to stressors. 34 The skills that are taught include social problem solving, communication skills training (e.g., assertiveness and social skills training), stress management, and cognitive-behavioral modification.…”
Section: Coping Skills Trainingmentioning
confidence: 99%
“…These demands are accompanied by cognitive shifts that provide for greater efficiency that contribute to more habitual styles of solving problems. During middle childhood, children practice problem-solving skills as they moderate the intensity and difficulties associated with educational transitions (Elias et al, 1986) and buffer the effects of stress on academic achievement and behavior (Dubow & Tisak, 1989). In fact, strong social problem solving in middle childhood has ripple effects on later development and shepherds a proficient shift into the workforce in early adulthood (Hustson & Ripke, 2006).…”
Section: Putting It All Together: How Practice Skills Are Learnedmentioning
confidence: 99%